Education, training and registration of Medical Physics Experts across Europe. (May 2021) - Maas, Ad J.J.; Lammertsma, Adriaan A.; Agius, Sam; Bert, Christoph; Byrne, Brenda; Caruana, Carmel J.; Gilligan, Paddy; Koutsouveli, Efi; Pace, Eric; Brambilla, Marco
Highlights: This survey concerns the education, training and registration of medical physics experts (MPEs). The survey, which covered all fields of interest for medical physicists, was closed in May 2020. The survey had a high response rate of 91% (33 out of 36 countries). The results give a good overview of how medical physicists are educated and trained in Europe. Recommendations are presented concerning uniformity in National Registration Schemes for MPEs. Abstract: From its inception, EFOMP has pursued a policy to improve and coordinate education and training of medical physicists across all its participating European countries. Several EFOMP policy statements on education and training have been published and surveys have been held to get an overview of the actual situation. At the beginning of 2020 a new survey was distributed amongst the 36 National Member Organizations (NMOs), in which questions were based on recommendations published in the most recent policy statements. Thirty-three of the NMOs (91%) responded, of which 22 indicated having a National Registration Scheme (NRS) for Medical Physics Experts (MPEs) in place. Another 6 indicated considering such a scheme. Results of the questionnaire showed that there was good correspondence between education and training programmes, i.e. a division between a BSc phase, an MSc phase and a clinical phase after completion of the MSc. Differences between NRSs were primarily seen in the availability and composition of a supervising committee and in the availability of guidelines for handling professional misconduct. In addition, some differences were seen in the topics that were part of the education and training programme. The goal of a universal (registered) MPE accepted by all European countries is still far away despite the progress being made. The new procedure for approving an existing NRS, which fulfils all EFOMP criteria is seen as an important step forward. Exchange of experience, knowledge, ideas and, above all, MPE trainees between European countries is seen as the best approach to achieve this goal.